2000
DOI: 10.1016/s0304-3975(98)00264-3
|View full text |Cite
|
Sign up to set email alerts
|

On the competitiveness of the move-to-front rule

Abstract: We consider the list access problem and show that one questionable assumption in the original cost model presented by Sleator and Tarjan (1985) and subsequent literature allowed for several competitiveness results of the move-to-front rule (MTF). We present an o-line algorithm for the list access problem and prove that, under a more realistic cost model, no on-line algorithm can be c-competitive for any constant c, MTF included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Martínez and Roura [29] and Munro [30] observed that in a realistic setting, rearranging the first i items of the list according to a permutation of {1, . .…”
Section: Preliminaries and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Martínez and Roura [29] and Munro [30] observed that in a realistic setting, rearranging the first i items of the list according to a permutation of {1, . .…”
Section: Preliminaries and Related Workmentioning
confidence: 99%
“…In subsequent work, Martínez and Roura [29] and Munro [30] independently argued that the standard-cost model penalizes reasonable algorithms which in practice can be quite efficient. Instead, they proposed a different cost formulation (to which, following [5] we refer as the modified-cost model) and showed that every online algorithm has asymptotically the same, non-constant competitive ratio, namely Θ(l/log l), where l is the size of the list.…”
Section: Introductionmentioning
confidence: 99%
“…While list update algorithms with better competitive ratio tend to have better performance in practice the validity of the cost model has been debated. More precisely, Martínez and Roura [18] and Munro [19], independently addressed the drawbacks of the standard cost model. Let (a 1 , a 2 , .…”
Section: Introductionmentioning
confidence: 99%
“…Our main result proves that under both the standard and the modified cost functions MTF is never outperformed in our model, while it always outperforms any other on-line list update algorithm in at least one instance. As mentioned earlier, Martínez and Roura [18] posed the open problem of finding an alternative measure that shows the superiority of MTF in the modified cost model and suggested that this can be done by adding some restrictions over the sequences of requests. Our analysis technique allows us to resolve this problem as well.…”
Section: Introductionmentioning
confidence: 99%
“…Some other algorithms, such as the Timestamp algorithm [2] are also 2-competitive in this model. In subsequent work, Martínez and Roura [25] and Munro [26] independently argued that the standard-cost model penalizes reasonable algorithms which in practice can be quite efficient. Instead, they proposed a different cost formulation (to which, following [4] we refer as the modified-cost model) and showed that every online algorithm has asymptotically the same, non-constant competitive ratio, namely Θ(l/log l), where l is the size of the list.…”
Section: Introductionmentioning
confidence: 99%